2017
DOI: 10.1111/josi.12234
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mother–Adolescent Relationship as a Promotive Resource for Sexual and Gender Minority Youth

Abstract: Research often analyzes gender minority youth and sexual minority youth as a single group, a practice that obscures differences in how gender identity and sexual orientation shape health. The present study uses intersectionality to explore similarities and differences in the relationships between minority stress theory variables in a sample of 28 gender minority and 135 sexual minority youth of color. We also explore the mother-adolescent relationship as a potential promotive resource for minority stress resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…1 The study findings are generally in line with previous research on suicide ideation and attempt within youth samples, which have identified victimization, lack of family and friend support, poor self-concept, and depressive symptoms as risk factors, [31][32][33][34] as well as research with TGNC samples that have found similar relationships. 2,5,8,12,15,[20][21][22][23][24] The findings are also consistent with the minority stress perspective, which emphasizes the role of both minority-specific and general factors in explaining higher rates of mental health concerns. [16][17][18][19] Nearly all proposed predictors were correlated with all three suicide-related outcomes and each set of factors (demographics, minority stress, social support, and depressive symptoms) explained significant variance in each outcome.…”
Section: Discussionsupporting
confidence: 78%
“…1 The study findings are generally in line with previous research on suicide ideation and attempt within youth samples, which have identified victimization, lack of family and friend support, poor self-concept, and depressive symptoms as risk factors, [31][32][33][34] as well as research with TGNC samples that have found similar relationships. 2,5,8,12,15,[20][21][22][23][24] The findings are also consistent with the minority stress perspective, which emphasizes the role of both minority-specific and general factors in explaining higher rates of mental health concerns. [16][17][18][19] Nearly all proposed predictors were correlated with all three suicide-related outcomes and each set of factors (demographics, minority stress, social support, and depressive symptoms) explained significant variance in each outcome.…”
Section: Discussionsupporting
confidence: 78%
“…Chaudoir, Wang, and Pachankis () discuss tools that social issues researchers can employ to promote coping with stigma to reduce disparities specifically for sexual minorities. Bouris and Hill () examine the mother–adolescent relationship as a promotive resource in context of sexual and gender minority youth of color. Finally, as the healthcare context emerges as one main area that intergroup relations research becomes relevant, Smith and Turell () presents a qualitative analysis of focus group data, describing healthcare experiences and best practices in healthcare encounters, calling for further training among healthcare providers to reduce disparities through improved patient–provider interactions (or intergroup relations) with sexual and gender minorities.…”
Section: The Current Journal Of Social Issues (Jsi) Volumementioning
confidence: 99%
“…For example, TGD youth with strong family relationships were less likely to experience mental health problems or engage in substance abuse than those with tenuous family relationships. However, findings from the limited number of studies specifically addressing sexual health outcomes among TGD youth were mixed, and relied on samples limited in size and ethnic diversity 14,34–36 . Furthermore, samples from these studies included youth assigned male at birth (AMAB) nearly exclusively; youth assigned female at birth (AFAB) were included in only one study, and fewer than 3% of the sample reported being AFAB.…”
Section: Family Relationships and Tgd Sexual Healthmentioning
confidence: 99%
“…However, fi ndings from the limited number of studies specifi cally addressing sexual health outcomes among TGD youth were mixed, and relied on samples limited in size and ethnic diversity. 14,[34][35][36] Furthermore, samples from these studies included youth assigned male at birth (AMAB) nearly exclusively; youth assigned female at birth (AFAB) were included in only one study, and fewer than 3% of the sample reported being AFAB. This limitation is concerning, because associations between specifi c risky sexual behaviors and parent or family connectedness often vary on the basis of sex assigned at birth.…”
Section: Family Relationships and Tgd Sexual Healthmentioning
confidence: 99%